The ability of postgraduate students in understanding the course of art education curriculum study at Institut Seni Budaya Indonesia Bandung - Nurudin Nurudin (Inovasi Kurikulum, 2025)
This study explores the perceptions of Master's students in the Art Education Study Program regarding their understanding of the Curriculum Studies in Art Education course at the Indonesian Institute of Arts and Culture in Bandung, indicating that they possess adequate knowledge and readiness, as well as the ability to implement it creatively and innovatively. The research identifies five key aspects of their understanding: 1) the direction and objectives of the course; 2) the definition and benefits of the curriculum; 3) the concept and models of curriculum development; 4) the relevance of art education in the educational system; and 5) the implementation of art education as a means of advancing knowledge. A total of 17 students participated by completing a questionnaire via Google Forms. The Respondents' Achievement Level (RAL) indicated a very high result, reflecting a deep understanding and a strong ability to apply the concepts effectively. It can be concluded that Master's students in Art Education at ISBI Bandung understand, master, or meet the expected standards in art education curriculum studies. Furthermore, the study encourages these students to analyze, evaluate, and develop art education curricula aligning with contemporary demands and local and global contexts.   Abstrak Penelitian ini mengeksplorasi persepsi mahasiswa S2 Program Studi Pendidikan Seni terhadap pemahaman mereka mengenai mata kuliah Kajian Kurikulum Pendidikan Seni di Institut Seni Budaya Indonesia Bandung, yang menunjukkan bahwa mereka memiliki kemampuan dan kesiapan ilmu yang memadai serta mampu mengimplementasikannya secara kreatif dan inovatif. Penelitian ini mengidentifikasi lima aspek pemahaman materi mata kuliah kajian kurikulum pendidikan seni, yaitu; 1) Arah dan tujuan mata kuliah kajian kurikulum pendidikan seni; 2) Pengertian, fungsi, dan manfaat kurikulum; 3) Konsep kurikulum, landasan kurikulum, dan model-model pengembangan kurikulum; 4) Pendidikan seni dalam dunia pendidikan kaitannya dengan kurikulum; dan 5) Implementasikan pendidikan seni sebagai pengembangan ilmu pengetahuan. Sebanyak 17 mahasiswa S2 berpartisipasi memberikan persepsinya melalui kuesioner dengan Google Form. Hasil Penelitian mengungkapkan lima aspek pemahaman tentang materi kajian kurikulum pendidikan yang terdiri dari 65 pernyataan. Tingkat pencapaian responden (Respondents' Achievement Level/RAL) menunjukkan hasil yang sangat tinggi, yang mencerminkan pemahaman yang mendalam serta kemampuan responden dalam menerapkan konsep dengan sangat baik. Dapat disimpulkan mahasiswa S2 Pendidikan Seni ISBI Bandung memahami, menguasai, atau memenuhi standar yang diharapkan dalam materi kajian kurikulum pendidikan seni. Penelitian ini mengarahkan mahasiswa untuk mampu menganalisis, mengevaluasi, serta mengembangkan kurikulum pendidikan seni yang sesuai dengan kebutuhan zaman dan konteks lokal maupun global. Kata Kunci: kajian kurikulum; mata kuliah; pendidikan seni